Kepastian Hukum dalam Proses Perceraian Talak di Hadapan dan Melalui Izin Mahkamah Negara Bagian dan Wilayah Persekutuan Malaysia - Az-Zahra Aulya Salsabila (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Divorce that occurs outside and without permission from the court raises many legal problems, from the validity of the divorce to the non-fulfillment of the rights and obligations of husband and wife after divorce. Malaysia is a country consisting of states and an alliance area which in its Islamic family law rules regulates divorce before the court to ensure legal certainty. This paper discusses the procedures for the divorce of Malaysian citizens that must be carried out before the Malaysian Court and the rules for registering talak for divorces that have already occurred not in front of and without the permission of the Malaysian Court. The regulations for imposing divorce outside the Malaysian Court also include penalties (punishment) for violators. This paper uses a juridical-philosophical approach to explain the procedure for divorce before the court and the rules related to the registration of divorce that have been carried out outside and without the truth of the court to create legal certainty. This research is a qualitative type of literature research. The conclusion of this paper shows that the rules related to divorce before the Malaysian Court indicate legal certainty because in the process the judge examines the validity of the lafadz talak that the husband has imposed to ensure the validity of the legal status of divorce in Sharia and the state administratively, as well as the fulfillment of the rights and obligations of husband and wife after divorce.